Polymer nanoparticles pass the plant interface - Sam J. Parkinson; Sireethorn Tungsirisurp; Chitra Joshi; Bethany L. Richmond; Miriam L. Gifford; Amrita Sikder; Iseult Lynch; Rachel K. O’Reilly; Richard M. Napier (Nature Communications, 2022)
Nanoplastic contamination is a serious environmental concern and could have implications on plant life depending upon interactions. Here, the authors study the effect of size and charge on the accumulation and uptake of model polymer nanoparticles by plant roots which has implications for environmental exposure and nanoparticle delivery to plants.